﻿Dietary habits change of Lessepsian migrants’ fish from the Red Sea to the Eastern Mediterranean Sea - Rami Tsadok; Ziv Zemah-Shamir; Eli Shemesh; Stephane Martinez; Debra Ramon; Itai Kolski; Anat Tsemel; Dan Tchernov (Aquatic Invasions)
As impacts on the Mediterranean Sea are expected to grow in the future, especially with climate change, habitat degradation, and displacement of native species by non-indigenous species (NIS), the investigation of significant alterations to trophic levels in this diverse marine habitat is important. Analysis of stable isotopes from targeted consumers has previously been shown to reliably reflect that of primary producers, thus enabling us to describe and highlight potential shifts in the food web of a particular ecosystem. In this study, we used δ13C values of essential amino acids (AA) in order to examine the dietary composition of established non-native, Lessepsian fish migrants in the Eastern Mediterranean Sea compared to that of the same fish species from their original population in the Gulf of Aqaba, Red Sea. Our data show that a clear variance in carbon isotopic signatures exists in food sources consumed by the same species between the different environments, with the exception of the classic herbivore, Siganus rivulatus (Forsskål & Niebuhr, 1775), whose very similar isotopic patterns reflect the algal source they predominantly consume in both locations. With the results of this research, we propose that Lessepsian fishes with the ability to maintain their nutritional patterns, though not necessarily that of their original food source, will acclimatize better in their new habitat. Consequences of flourishing Lessepsian fish populations include a further tropicalization of the Eastern Mediterranean Sea and the likely restructuring of local food webs.